Pengaruh Model Pembelajaran CIRC dan Gerakan Literasi Sekolah terhadap Kemampuan Pemahaman Membaca Peserta Didik SD - Adhi Kurniawan; Yepi Sedya Purwananti, Rahyu Setiani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Reading comprehension ability is a fundamental competency essential for academic success, but observations in the field show that many students have difficulty understanding texts. This type of quasi-experimental research with a non-equivalent control group design aims to test the partial and simultaneous effects of CIRC and GLS on the reading comprehension of fifth grade students. Data from 20 learners (experimental) and 15 learners (control) were collected through tests and questionnaires, then analyzed with t and F tests. The results showed that CIRC (p=0.005) and GLS (p=0.031) had a significant effect partially. Simultaneously, both were also highly significant (p<0.001). The experimental group showed a significant increase in post-test score (average increase of 4.150 points, p<0.001), in contrast to the control group which was not significant (p=0.638). This study confirms that CIRC and GLS, both partially and simultaneously, significantly improve the reading comprehension of primary school students.